Application of A New Bio-Formulation of Chaetomium cupreum For Biocontrol of Colletotrichum gloeosporioides Causing Coffee Anthracnose on Arabica Variety in Laos - Somlit Vilavong; Kasem Soytong (AGRIVITA, Journal of Agricultural Science, 2017)
The anthracnose pathogen was isolated from coffee leave and bean symptoms. Morphological and molecular phylogenetic data confirmed the species as Colletotrichum gloeosporioides. The pathogenicity of the isolate was also confirmed by detached leaf method which inoculated the virulent isolate into coffee leaves. The crude extracts with hexane, ethyl acetate and methanol solvents from Chaetomium cupreum CC3003 resulted significantly inhibited C. gloeosporioides that the ED50 values of 13, 11 and 28 ppm, respectively. The bioactive substances of C. cupreum CC3003 expressed antifungal activity against C. gloeosporioides as can be seen in the abnormal appearance of spores. A powder bio-formulation of C. cupreum significantly resulted to reduce anthracnose disease of 54.77 %. The application of nano-rotiorinol, nano-trichotoxin and a spore suspension of C. cupreum reduced anthracnose incidence of 46.23, 42.71 and 18.59 %, respectively while the inoculated control had high anthracnose disease. The application of bio-formulation of C. cupreum in powder form, nano-rotiorinol, and nano-trichotoxin to reduce coffee anthracnose was reported for the first time in Lao PDR.